Ultra wideband channel coefficient measurements for detecting methane gas in a multipath environment. Issue 3 (2nd July 2016) - Alshabo, Ahmed; Stirling, David; Ros, Montserrat; Vial, Peter James; Wysocki, Beata Joanna; Wysocki, Tadeusz Antoni; Sasso, Nicholas Dal
Abstract: In this paper, an investigation was carried out into the effect of a non-explosive methane gas mixture on various ultra wide band channel coefficients. Using simplified apparatus consisting of a rubberised tube (6 mm diameter) connected for significant periods to either a (pressurised) source of mixed methane and nitrogen or alternatively to a nitrogen only source. The tube containing either gas feed was wrapped using two complete turns around a 160 mm diameter PVC pipe. Several flows of the mixed gas, containing 2.57% methane, were introduced and flowed through the pipe before being sealed in the tube. Removal of any methane in the tube was achieved by flushing it with the pure nitrogen source, initially and in-between samples of the mixed source. A Vector Network Analyser was connected using two identical directional antennas with the wrapped section of tubing placed between the two antennas and the wireless channel coefficients were measured over the ultra wide band frequency span of 0.3–8 GHz. Magnitude differences were taken between the baseline condition (tube flushed out with nitrogen) and alternatively containing the methane mixture. It was found that consistent and repeatable experiments produced the same trend of differences over the same frequency span. This system based on this approach could thus be used as a simple sensor to detect the accumulation of methane gas in an environment well before it becomes explosive at around a concentration of 5%.